Assessing the Consistency of Political Attitude and Position of Melanesian Countries on the Papua Issue in International Forums [Memahami Konsistensi Sikap Politik Negara-Negara Melanesia mengenai Isu Papua di Forum Internasional] - Andreas Brian Bagaskoro Bayuseno; Reni Windiani (Jurnal Politica, 2020)
Melanesian countries such as Vanuatu, Solomon Island, Tonga, New Caledonia, Tuvalu, Nauru, and Marshall Islands often raise the Papua human rights issue in international forums. While Indonesia has already explained and provided a clear statement about Papua, Melanesian countries remain firm in their solidarity with Papua. This research seeks to find the answer why Melanesian countries keep raising the Papua human rights issue in international forums and denouncing Indonesia. The author employs the Non-Western International Relations Theory from Ibn Khaldun, particularly on the asabiyyah concept with 3 variables -- tribe, human needs or something to fight for, and religion -- to analyze the study case. The research finds that Melanesian countries’ conducts are based on the sense of unity and collective consciousness between Papua and Melanesian countries. The bond of association and religion between Papua and Melanesian people also plays a critical role in this regard. Human needs that is identified as Human Rights for the Papuan people is the shared human needs that Melanesian people fight for.AbstrakNegara-negara Melanesia seperti Vanuatu, Kepulauan Solomon, Tonga, Kaledonia Baru, Tuvalu, Nauru, dan Kepulauan Marshall kerap kali membawa permasalahan HAM Papua dalam forum-forum internasional. Meskipun Indonesia sudah menjelaskan dan memberikan clear statement terkait isu di Papua, namun negara-negara Melanesia tetap solid untuk membantu Papua dan membawa isu Papua. Penelitian ini berusaha untuk mencari jawaban mengapa negara-negara Melanesia terus-menerus membawa isu Papua dalam forum-forum internasional dan mengecam Indonesia. Penulis menganalisis studi kasus dengan menggunakan Non-Western International Relations Theory dari Ibn Khaldun, khususnya konsep asabiyyah dengan 3 (tiga) variabel yakni kesukuan, kebutuhan atau apa yang diperjuangkan, dan agama. Penelitian ini menemukan bahwa tindakan negara-negara Melanesia tersebut didasari oleh rasa persatuan dan kesadaran kolektif antara Papua dengan negara-negara Melanesia. Adanya ikatan rasa persaudaraan dan agama antara masyarakat Papua dan Melanesia juga turut berpengaruh. Kebutuhan manusia yang diidentifikasikan sebagai Hak Asasi Manusia bagi orang Papua adalah kebutuhan bersama yang diperjuangkan oleh orang Melanesia.